Multi-functional approach in the design of smart surfaces to mitigate bacterial infections: a review - Rajaramon, Shobana; David, Helma; Sajeevan, Anusree; Shanmugam, Karthi; Sriramulu, Hrithiha; Dandela, Rambabu; Solomon, Adline Princy (Frontiers in Cellular and Infection Microbiology, 2023)
Advancements in biomedical devices are ingenious and indispensable in health care to save millions of lives. However, microbial contamination paves the way for biofilm colonisation on medical devices leading to device-associated infections with high morbidity and mortality. The biofilms elude antibiotics facilitating antimicrobial resistance (AMR) and the persistence of infections. This review explores nature-inspired concepts and multi-functional approaches for tuning in next-generation devices with antibacterial surfaces to mitigate resistant bacterial infections. Direct implementation of natural inspirations, like nanostructures on insect wings, shark skin, and lotus leaves, has proved promising in developing antibacterial, antiadhesive, and self-cleaning surfaces, including impressive SLIPS with broad-spectrum antibacterial properties. Effective antimicrobial touch surfaces, photocatalytic coatings on medical devices, and conventional self-polishing coatings are also reviewed to develop multi-functional antibacterial surfaces to mitigate healthcare-associated infections (HAIs).